Radiotherapy for prostate cancer: DISCERN quality assessment of patient-oriented websites in 2018 - Janssen, S.; Fahlbusch, F. B.; Kaesmann, L.; Rades, D.; Vordermark, D. (BMC Urology, 2019)
Background: Prostate cancer is the most commonly diagnosed cancer in men. Radiotherapy represents one major treatment option in different therapeutic settings. As patients increasingly rely on internet-based medical information, we examined the quality of information on radiotherapy and prostate cancer in websites used by laypersons. Methods: An Internet search from a patients' perspective was carried out using different search engines (Google, Yahoo and Bing, search terms: "prostate cancer" and "radiotherapy"). The quality of search results was analyzed with regard to the DISCERN score, HON code certification, the JAMA criteria and the ALEXA traffic rank. Results: In general, websites were of good quality. The highest quality was found for websites operated by charity organizations. No significant differences in results obtained via the above-mentioned tools were seen for the examined search engines, but Google revealed the most stable search results in terms of temporal changes. Conclusion: Patients with prostate cancer can sufficiently inform themselves on general treatment options including radiotherapy on websites directed at laypersons. However, no simple strategy could identify high quality websites in general. For treating physicians, it is important to support patients in interpreting and ranking the vast quantity of information.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Health-related information; Internet; Online information; Prostate cancer; Radiotherapy